Mosses at the bodogol natural conservation education center: species, diversity index, and evenness index - Rizhal Hendi Ristanto; Hany Qisthina Syhira; Alma Tasya Yuanisa; Aisha Amalia; Riezka Lianita; Ariella Azzahra; Diana Vivanti Sigit (STKIP Persada Khatulistiwa Sintang, 2021)
Mosses or Bryophytes are a group of cryptogamous plants or lower plants. Moss can be found in various places that have high humidity by attaching to various substrates, such as soil, rocks and tree bark. PPKA Bodogol is a potential area that protects endemic flora and fauna on the island of Java that has excellent humidity and air for moss growth and supports moss diversity. This study aims to determine the diversity of mosses and their relationship to environmental factors in the PPKA Bodogol. Data collection in this study was carried out at the PPKA Bodogol on 3 routes, namely Cikaweni, Rasamala and Kanopi. This research uses a purposive sampling method with a cover square technique. The results showed that the total number of moss species identified were 21 species. Then it was also known that the highest level of diversity was found on the Rasamala route with a diversity index of 3.03. In the Cikaweni route, was in moderate category, namely 1,967. The lowest diversity index, however, was in the canopy path with a medium category, namely 1.216. Environmental factors such as humidity, temperature, light intensity, and altitude also had an influence on the level of moss diversity of the three routes.